Judicial Considerations of Parental Attitudes in Child Custody Disputes: An Empirical Analysis in Ghana - Atupare, Peter Atudiwe; Yin, Elijah Tukwariba (Universitas Negeri Semarang, 2025)
The complexity of child custody disputes in family law has a significant impact on all parties involved, particularly the children. The effect of parental attitudes on custody decisions is substantial; however, very few empirical studies have focused on this issue. This paper examines the influence of parental attitudes on custody outcomes. Using the mixed-method approach, data were gathered from divorced parents, lawyers, and a judge. The analyzed data, through the lens of the Parental Responsibility Model, the Best Interests of the Child Standard, and established legal frameworks, emphasize the significance of emotional ties, daily care, and guidance on judicial outcomes in custody cases. It also emerged that parents who jointly prioritized their child’s needs were more likely to receive favourable custody decisions. The study concludes by emphasizing the need for a holistic approach to judicial decisions that accommodates the intricate relationship between parental emotional ties, daily care, and guidance.